Iceberg Motion in Lancaster Sound and Northwest Baffin Bay, Summer 1978 - de Lange Boom, B.R.; MacNeill, M.R.; Buckley, J.R. (ARCTIC, 1982)
A radar station on Hope Monument, Devon Island, N.W.T., was operated from 7 July 1978 to 24 September 1978 to track the movement of icebergs in eastern Lancaster Sound and northwestern Baffin Bay. Data were recorded by photographing the radar screen every 20 minutes. Meteorological measurements were also made. The data were processed by computer to provide a statistical picture of the iceberg motions as well as tracks of individual bergs. The mean circulation pattern of the ice was well defined and variations about the mean did not greatly change the general form of the pattern. The dominant feature of the flow was a stream of icebergs moving with a mean speed of about 40 cm/s southward along the east coast of Devon Island from north of Philpots Island to Cape Sherard and then westward to Cape Warrender. At Cape Warrender, the bergs turned toward the centre of Lancaster Sound with directions ranging from southwest to southeast and average speeds up to 50 cm/s. East of the coastal stream in Baffin Bay, the icebergs moved slowly (<25 cm/s) westward to join the coastal stream, while south of the stream at the entrance to Lancaster Sound two large persistent eddies were observed. In Baffin Bay, variations in the flow field appeared to be in response to direct meteorological forcing while in Lancaster Sound no evidence of this response was found. The variations in iceberg motion in the sound appeared to be caused by changes in the currents.Key words: iceberg motion, radar tracking, Baffin Bay, Lancaster Sound